2016
DOI: 10.5392/jkca.2016.16.03.219
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Usefulness of <sup>99m</sup>Tc-DMSA Renal SPECT Using High Sensitivity-All Purpose Collimator for Pediatric Patients

Abstract: Tc-DMSA planar scan that can analyze the functions of kidney quantitatively provides less information on a lesion than tomography scanning. Therefore, this study applied a high sensitivity all-purpose collimator that is sensitive to photonic signals to 99m Tc-DMSA and carried out a clinical scan with single photon emission computed tomography (SPECT). And diagnostic accuracy and time requirement of were analyzed to know the clinical usefulness of the applied scanning method. 10 subjects were intravenously inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The mismatching between static and SPECT images may return to renal impairment, high background activity or very small scars. Another study by Kim et al, [15] who found that SPECT images offered statistically significant value over static renal scintigraphy for detection of cortical defects, SPECT images found more lesions in kidneys by 21% than static images.…”
Section: Discussionmentioning
confidence: 94%
“…The mismatching between static and SPECT images may return to renal impairment, high background activity or very small scars. Another study by Kim et al, [15] who found that SPECT images offered statistically significant value over static renal scintigraphy for detection of cortical defects, SPECT images found more lesions in kidneys by 21% than static images.…”
Section: Discussionmentioning
confidence: 94%